Innovation in Information Systems and Technologies to Support Learning Research Proceedings of EMENA-ISTL 2019 - Serrhini, Mohammed; Silva, Carla; Aljahdali, Sultan (Learning and Analytics in Intelligent Systems, 2020)
XVII, 641 p. 308 illus., 236 illus. in color.